2003
DOI: 10.1007/s00439-003-1018-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin�26) in east Asians

Abstract: Mutations in the GJB2 gene encoding connexin 26 (Cx26) are a major cause of autosomal recessive and sporadic cases of congenital deafness in most populations. The 235delC mutation of GJB2 is the most frequent known mutation in some east Asian populations, with a carrier frequency of approximately 1%. In order to study the origin of 235delC among east Asians, we analyzed single-nucleotide polymorphisms (SNPs) within the coding region of GJB2 and flanking the 235delC mutation. We observed significant linkage dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 35 publications
7
101
0
Order By: Relevance
“…25 The role of the founder effect in the origin and distribution of several mutations of the GJB2 gene was well established. 7, [26][27][28][29][30] Furthermore, novel hypotheses for the probable specific mechanism (combination of improved genetic fitness and assortative mating) for selective amplification of the commonest form of recessive deafness in the populations and of probable heterozygote advantage of GJB2 recessive mutations have been suggested. 31,32 Data on the mutation spectrum and prevalence of major mutations of the GJB2 gene in various ethnic groups are very important for the development of molecular diagnostics tools for identifying genetic causes of hereditary hearing loss; however, data on the prevalence of major GJB2 mutations in some populations are still not available.…”
Section: Introductionmentioning
confidence: 99%
“…25 The role of the founder effect in the origin and distribution of several mutations of the GJB2 gene was well established. 7, [26][27][28][29][30] Furthermore, novel hypotheses for the probable specific mechanism (combination of improved genetic fitness and assortative mating) for selective amplification of the commonest form of recessive deafness in the populations and of probable heterozygote advantage of GJB2 recessive mutations have been suggested. 31,32 Data on the mutation spectrum and prevalence of major mutations of the GJB2 gene in various ethnic groups are very important for the development of molecular diagnostics tools for identifying genetic causes of hereditary hearing loss; however, data on the prevalence of major GJB2 mutations in some populations are still not available.…”
Section: Introductionmentioning
confidence: 99%
“…However, a few GJB2 mutations have been described to be associated with autosomal dominant hearing loss [5]. Among the recessive mutations, 35delG is the most frequent in Caucasians, 167delT in Ashkenazi Jews, 235delC in East Asians, and R143W in Africans, suggesting the existence of founder effects in different ethnic groups [6][7][8][9][10][11][12][13][14][15][16][17][18]. In addition, some studies have shown the high prevalence of the IVS1 + 1G to A mutation in the non-coding part of the GJB2 gene [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…During data analyses, we have found that many well-known deafness-causing mutations are present in the dbSNP database. One of the best examples is rs80338943, which is the most common GJB2 deafness mutation (235delC) among the East Asians (Yan et al, 2003). There is definitely an urgent need for better SNP filters and annotation for helping find deleterious deafness mutations.…”
Section: Discussionmentioning
confidence: 99%